2020
DOI: 10.1175/wcas-d-19-0141.1
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t Tell Me What to Do”: Resistance to Climate Change Messages Suggesting Behavior Changes

Abstract: This study evaluates the impact of exposure to messages that emphasize the need for changes in individual behavior or in public policy to address climate change attributed to a “climate scientist” or to an unnamed source. We implemented a large survey-experiment (N=1,915) online through Amazon’s Mechanical Turk (MTurk) platform that manipulated the presence of recommendations for voluntary behavioral changes or the adoption of new laws to mitigate climate change. We found that, regardless of the source of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…Actions with greater mitigation potential reflect greater lifestyle changes and challenges for adoption. It is perhaps then not surprising a recent survey found that participants responded negatively to statements that individuals should take mitigation actions, finding it more palatable that other actors such as industry and businesses should be the ones taking action (Palm et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Actions with greater mitigation potential reflect greater lifestyle changes and challenges for adoption. It is perhaps then not surprising a recent survey found that participants responded negatively to statements that individuals should take mitigation actions, finding it more palatable that other actors such as industry and businesses should be the ones taking action (Palm et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…57,59 Experimental evidence appears to support this conclusion. Palm et al, 240 for example, observe that messages framed in terms of individual behavior not only ''decreased individuals' willingness to take personal actions'' but also ''decreased willingness to [take collective action such as to] support pro-climate candidates, reduced belief in the accelerated speed of climate change, and decreased trust in climate scientists.'' Illustrations of how narratives of individualized responsibility have protected fossil fuel interests from climate action are widespread.…”
Section: Individualized Responsibilitymentioning
confidence: 99%
“…Conversely, it is also possible that source expertise might be more influential with a more technical and complex message as in the absence of ability or motivation to fully comprehend the message, source expertise might be a heuristic for the likely veracity of the content. More broadly, expert opinion might be more effective at persuading in domains outside of policy advocacy, such as dispelling misinformation and promoting individual behavior change (Goldberg et al, 2020;Vraga & Bode, 2017, but also see Palm et al, 2020). Finally, the novelty and audiences' familiarity with issues is worth considering as persuasion and opinion change may be more likely on issues where individuals do not already have a firm opinion (McCroskey, 1969).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%